Analysis on loan processing and credit appraisal system of Habib Bank Limited, Bangladesh - Ali, Hamida Amir (BRAC University, 2011)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2011.